2022
DOI: 10.3389/fphar.2022.896108
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Osteoclast Effect of Exportin-1 Inhibitor Eltanexor on Osteoporosis Depends on Nuclear Accumulation of IκBα–NF-κB p65 Complex

Abstract: Osteoporosis affects around 200 million people globally, with menopausal women accounting for the bulk of cases. In the occurrence and development of osteoporosis, a key role is played by osteoclasts. Excessive osteoclast-mediated bone resorption activity reduces bone mass and increases bone fragility, resulting in osteoporosis. Thus, considerable demand exists for designing effective osteoporosis treatments based on targeting osteoclasts. Eltanexor (Elt; KPT-8602) is a selective nuclear-export inhibitor that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…Chen et al found that Eltanexor (Elt), a selective nuclear-export inhibitor, prevented NF-κB activity by trapping IκBα in the nucleus and protecting it from proteasomal degradation, thereby impeding the translocation of IκBα and NF-κB p65. Consequently, the inhibition of NF-κB suppressed NFATc1 and c-Fos activity and resulted in the downregulation of genes and proteins associated with bone destruction (Chen et al 2022a ).…”
Section: The Rankl/rank Signaling Pathway Activates Nfatc1mentioning
confidence: 99%
“…Chen et al found that Eltanexor (Elt), a selective nuclear-export inhibitor, prevented NF-κB activity by trapping IκBα in the nucleus and protecting it from proteasomal degradation, thereby impeding the translocation of IκBα and NF-κB p65. Consequently, the inhibition of NF-κB suppressed NFATc1 and c-Fos activity and resulted in the downregulation of genes and proteins associated with bone destruction (Chen et al 2022a ).…”
Section: The Rankl/rank Signaling Pathway Activates Nfatc1mentioning
confidence: 99%
“…Nevertheless, regenerating damaged bone tissue in osteoporosis patients remains a therapeutic challenge. Conventional antiosteoporotic medications can improve conditions to some degree but cannot effectively repair affected areas, with long-term use incurring more side effects (Li J. et al, 2022;Chen et al, 2022;Long et al, 2022;Wu et al, 2022). Therefore, searching for a safe and efficacious osteoporosis drug is imperative.…”
Section: Introductionmentioning
confidence: 99%